FROM COLLABORATION TO PARTICIPATION DEFICIT: DYNAMIC OF ENVIRONMENTAL CONSERVATION MOVEMENT IN RESPONDING TO TOURISM POLICY - Rachmad Kristiono Susilo (Magister Ilmu Administrasi Publik, 2025)
This research aims to describewater source conservation movement from collaboration to deficit participation and description of the cause of participation deficit. Method used was phenomenological qualitative approach. Result shows that tourism policy triggers the birth of environmental conservation movement. This movement departs from the actors’ concern with tourism development triggering land conversionand hotel development potentially damaging their water sources. Collaboration is built by actors with varying background including community activists, NGOs, and academicians. The movement-strategiesyielded include initiating, framing issues, coercingthe policy makers, meeting, lobbying, demonstrating, litigating, and regenerating. All decisions and executions result from “joint discussion (rembug bersama)”. Collaboration runs dynamically but unsustainably because of decreased quantity and qualityof actor participation in joint activities. This collaboration problem is due to participation deficit.Participation deficit is due to: a) structural condition, and b) collective interpretation level and individual experience level. The second factor is affected by lost main problem, ineffective leadership, and incomplete social facilitation. This research concludes that collaboration in community organization faces some constraints affected by the dynamics internal to movement and external to city.